2008
DOI: 10.1111/j.1471-4159.2008.05758.x
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin induces mitotic microtubule catastrophe and inhibits glioma cell invasion

Abstract: Doublecortin (DCX) is a microtubule (MT) binding protein that induces growth arrest at the G2-M phase of cell cycle in glioma and suppresses tumor xenograft in immunocompromised hosts. DCX expression was found in neuronal cells, but lacking in glioma cells. We tested the hypothesis that DCX inhibits glioma U87 cell mitosis and invasion. Our data showed that DCX synthesizing U87 cells underwent mitotic MT spindle catastrophe in a neurabin II dependent pathway. Synthesis of both DCX and neurabin II were required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 56 publications
3
48
0
2
Order By: Relevance
“…In line with this behavior, SPN has been shown to bind to the PP1-doublecortin complex, inducing its dephosphorylation 43 and inhibiting anchorage-independent growth in glioma cells. [44][45][46] In contrast, doublecortin-mediated growth repression is lost in the absence of Spn.…”
Section: Discussionmentioning
confidence: 95%
“…In line with this behavior, SPN has been shown to bind to the PP1-doublecortin complex, inducing its dephosphorylation 43 and inhibiting anchorage-independent growth in glioma cells. [44][45][46] In contrast, doublecortin-mediated growth repression is lost in the absence of Spn.…”
Section: Discussionmentioning
confidence: 95%
“…19 A more detailed description of the assessment of mitotic catastrophe is presented in the supplemental Methods.…”
Section: Cell Growth and Viability Assaysmentioning
confidence: 99%
“…Other studies have also suggested a role for Dcx in mediating the cross talk between the actin and microtubule cytoskeleton (Tsukada et al, 2005; Coquelle et al, 2006; Bielas et al, 2007; Santra et al, 2009). However, changes in the actin structure/function in Dcx mutant or RNAi treated neurons have not previously been reported, most likely because the actin phenotype is not as severe in single mutants compared with Dcx−/y; Dclk1−/− neurons.…”
Section: Introductionmentioning
confidence: 96%